Retos y avances del cáncer de pulmón de células no pequeñas metastásico EGFR mutado - Castro-Mollo, M (2024)
Introduction: Tyrosine kinase inhibitors have dramatically changed the clinical outcomes for patients with advanced non-small cell lung cancer with epidermal growth factor receptor mutations. However, there are still challenges in the management of patients with this mutation in a metastatic setting, such as intrinsic and acquired resistance to tyrosine kinase inhibitors. We will discuss the latest advances and new strategies in first-line treatment, osimertinib resistance, and exon 20 mutation treatment. © 2024 Universidad Ricardo Palma, Facultad de Medicina Humana. All rights reserved.